Hypothalamic FTO upregulates BDNF to promote GnRH expression through the PI3K/Akt pathway, leading to precocious puberty - Zang, Shaolian; Ouyang, Yang; Li, Pin; Yin, Xiaoqin (Frontiers in Endocrinology, 2025)
BackgroundPuberty is among the most important stages in human development. Timely activation of hypothalamic gonadotropin-releasing hormone (GnRH) neurons underlies the initiation of pubertal development. The fat mass and obesity-associated (FTO), which is expressed in the hypothalamus, may regulate the m6A methylation of its target genes, influencing GnRH expression in the hypothalamus during puberty onset. This study aimed to explore the mechanism by which FTO regulates the function of its target neurotrophins within the hypothalamus and to clarify the molecular pathway underlying precocious puberty.MethodsMethylated RNA immunoprecipitation sequencing (MeRIP-seq) was used to assess m6A methylation in the hypothalamus of female rats. Serum brain-derived neurotrophic factor (BDNF) levels were measured in girls with central precocious puberty (CPP) and matched controls. BDNF was applied to GnRH neurons in vitro. The functions of FTO were assessed through overexpression and knockdown in animal models, with downstream signaling evaluated via BDNF/PI3K/Akt pathway analysis. Intracerebroventricular (ICV) injections of a BDNF-overexpressing lentiviral vector or a negative control (NC) were used to investigate the role of central BDNF in regulating puberty onset and reproductive function.ResultsHypothalamic GnRH and FTO expression progressively increased whereas m6A methylation decreased during puberty. MeRIP-seq revealed significantly reduced m6A methylation of Bdnf mRNA in the arcuate nucleus (ARC) of female rats during early puberty. In the ARC, BDNF was expressed adjacent to GnRH-positive fibers and terminals. In addition, serum BDNF levels were higher in girls with CPP girls than in the control group. In vitro, BDNF treatment stimulated GnRH expression in GT1–7 cells. FTO positively regulated BDNF expression in an m6A methylation-dependent manner. FTO overexpression activated BDNF/PI3K/Akt signaling in the ARC and accelerated puberty onset. Conversely, FTO knockdown delayed vaginal opening and suppressed BDNF/PI3K/Akt signaling. ICV delivery of a BDNF-overexpressing lentivirus increased hypothalamic BDNF and GnRH expression, leading to a distinct endocrine profile.ConclusionThese findings suggest that FTO regulates the m6A demethylation of BDNF and promotes GnRH expression through the BDNF/PI3K/Akt signaling pathway. This study improves our understanding of the function of BDNF, which is critical for the development of therapeutic strategies for preventing and treating of precocious puberty.